2002
DOI: 10.1352/0047-6765(2002)040<0191:pfstcg>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Providing Family Support Through Community Guides

Abstract: The Family Support Opportunities program in the state of Washington has a unique component. People with extensive knowledge of local communities, referred to as community guides, were made available to all families enrolled in the program. Community guides assisted families by seeking information about community resources that families needed and helping families connect to those resources. Responses from a survey of 312 families were analyzed to determine the impact of the community guides' services. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Psychoeducational programs for parents of children with disabilities should help families obtain information about services for their child and find out how to locate and avail themselves of existing resources, and should provide information regarding the access to respite services so that parents can take a break from the heavy demands of looking after their child (Ellis et al., ; Romer, Richardson, Nahom, Aigbe, & Porter, ).…”
Section: Introductionmentioning
confidence: 99%
“…Psychoeducational programs for parents of children with disabilities should help families obtain information about services for their child and find out how to locate and avail themselves of existing resources, and should provide information regarding the access to respite services so that parents can take a break from the heavy demands of looking after their child (Ellis et al., ; Romer, Richardson, Nahom, Aigbe, & Porter, ).…”
Section: Introductionmentioning
confidence: 99%
“…Kutash et al () reported a moderate effect size for increase in school‐based mental health service use among intervention youth with emotional disturbances. The only exception was Romer's et al () study of a community guide intervention. Families satisfied with their guides did not differ from “no guide” families in terms of finding specific support services.…”
Section: Resultsmentioning
confidence: 99%
“…Of 19 studies that provided caregiver data, seven (Chernoff, Ireys, DeVet, & Kim, ; Ireys, Chernoff, DeVet, & Kim, ; Magaña, Lopez, & Machalicek, ; Pilon & Smith, ; Silver, Ireys, Bauman, & Stein, ; Sullivan‐Bolyai et al, , ) targeted mothers; one (Sullivan‐Bolyai, Bova, Lee, & Gruppuso, ) focused on fathers; six included either parent (Jerram, Raeburn, & Stewart, ; Kieckhefer et al, ; Picard, Morin, & De Mondehare, ; Singer et al, ; Swallow et al, ; Thomas et al, ); two included parent dyads (Dellve, Samuelsson, Tallborn, Fasth, & Hallberg, ; Schultz et al, ); and three included grandparents along with biological, adopted, or step parents (Farber & Maharaj, ; Ireys, Sills, Kolodner, & Walsh, ; Kutash, Duchnowski, Green, & Ferron, ). Seven studies focused on children with a variety of chronic health conditions (Chernoff et al, ; Dellve et al, ; Hixson, Stoff, & White, ; Ireys et al, ; Jerram et al, ; Kieckhefer et al, ; Pless & Satterwhite, ); five focused on children with specific chronic conditions such as juvenile rheumatoid arthritis (Ireys et al, ), diabetes (Sullivan‐Bolyai et al, , , ), or chronic kidney disease (Swallow et al, ); six studies included children with developmental or intellectual disabilities (Farber & Maharaj, ; Magaña et al, ; Picard et al, ; Pilon & Smith, ; Romer, Richardson, Nahom, Aigbe, & Porter, ; Schultz et al, ); two studies included children with both chronic health conditions or developmental disabilities (Silver et al, ; Singer et al, ); and two studies focused on youth with emotional or mental health conditions (Kutash et al, ; Thomas et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations